The transfer of family businesses in Northern Germany and Austria - Thomas Glauben; Hendrik Tietje; Stefan Vogel (Kiel University, Department of Food Economics and Consumption Studies, 2004)
The transfer of family businesses from one generation to the next can be considered as an event with far-reaching effects for the business. Investments and decisions about restructuring the business are closely tied to succession considerations. This paper analyzes successions plans in the primary sector using a survey conducted in 2003 of 348 farmers in Schleswig-Holstein (Northern Germany) and 278 farmers in Austria. Three samples were obtained: full time farmers in Schleswig-Holstein, full time farmers in Austria and part time farmers in Austria. The structure of the farm sector in both countries differs in several ways: Farmers in Schleswig-Holstein operate on larger scales, are more market oriented and use more intensive production technologies than their Austrian counterparts. In addition, Austrian farmers have distinct traditional attitudes in farming and are likely located in disadvantaged areas on average. The analysis focuses on differences in succession plans and farm family characteristics in the three samples. This encompasses the fact that farms in Schleswig-Holstein have proportionally higher rates of identified successors and farm adjustment plans than in Austria. Results also show that there are not only significant differences in farm succession patterns, but also in value systems.
Keywords: 330